The Development of Learning Video Media for Earthquake Themes Using Four-Step Teaching Materials Development (4S-TMD) - Nurul Safira; Sahrul Saehana (Berkala Ilmiah Pendidikan Fisika, 2020)
This research was conducted to develop and know the quality and feasibility of learning video media for the earthquake theme using four-step teaching materials development (4S-TMD). This research is a type of research and development that refers to Borg and Gall's development design. This study's subjects were students of class XI IPA Al-Qomar (N = 18) MAN Insan Cendekia Palu. Data collection was done by using a questionnaire method. The validation data analysis results of material experts and media experts show an average score of 3, or with a percentage of 75% with a good category, the teacher's assessment shows an average score of 3.84 in a good category. Students' responses show an average score of 3.28, or with a percentage score of 82% with the category agree completely. The results of this study indicate that the earthquake theme learning video media developed using four-step teaching materials development (4S-TMD) is feasible and can be used as a learning medium. This research implies that the teaching media that are processed using appropriate methods make learning more interesting. The resulting instructional videos can also be used as learning media in class, in groups, or independently.